CURRENT CONDITIONS FOR THE PROVIDENT OF CIVIL MEASURES CONTRA DROGS CONTRACTING CLASS I PARTIELLE ON THE BASIS OF LEGISLATION No. 35 OF 2009 ON DRUGS (Study of Judgment No. 446/Pid.Sus/2020/PN.Gpr) - Jasa Sudjana; Deny Guntara; Yuniar Rahmatiar (Justisi: Jurnal Ilmu Hukum, 2023)
Narcotics abuse is an act of crime, the problem of narcotics abuse has a very negative and detrimental impact both in terms of law, health, economics, politics, and socio-cultural life. Narcotics abuse has been regulated in Article 127 of Law No. 35 of 2009 concerning Narcotics. As for the identification of the problem in this research study regarding the imposition of punishment against the perpetrators of the crime of class I drug abuse for themselves according to Law No. 35 of 2009 concerning Narcotics and what are the considerations of the panel of judges in deciding a case against the perpetrators of the crime of class I drug abuse for themselves himself in decision no 446/Pid.Sus/2020/PN.Gpr. In this study the aims were to find out the sentence imposed on the perpetrators of the crime of class 1 narcotics abuse for themselves according to Law No. 35 of 2009 and to find out the considerations of the panel of judges in deciding a case against the perpetrators of the crime of class I narcotics abuse for themselves in the decision number 446/Pid.Sus/2020/PN.Gpr. The research method used in this study is a normative juridical research method using secondary data as the main data. The results of this study are based on Law No. 35 of 2009 concerning Narcotics that perpetrators of class I drug abuse for themselves should receive medical and social rehabilitation, and the Decision of the Kediri District Court Number 446/Pid.Sus/2020PN.Gpr according to researchers there was a mistake and not in accordance with Law No. 35 of 2009 concerning Narcotics.